Media Komunikasi Dakwah Dalam Foto Jurnalistik (Analisis Interpretatif Foto Jurnalistik di Halaman Edisi Cahaya Ramadhan Republika) - Iin Yuniarni (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
Photo journalism is one part that is attached to the print media. The print media has a major role in setting the agenda and opinion formation. The purpose of this research is meant to get the meaning of photojournalism that can be used as communication media propaganda with scientific knowledge that supports it. This type of research is using qualitative interpretative approach semiotic model of Roland Barthes. From the results of media research photojournalism can be used as a means of communication propaganda effective with the proviso that photo-charged propaganda, photo selection of effective, photos soothing reader / audience, images that can evoke unity not stuck confrontation with other religious faiths, not pitched provocation, not moreover erotic photographs of objects that are forbidden by Islam.